Phenotypic and genotypic characterization, and detection of PVL encoding gene in methicillin resistant staphylococcus aureus strains isolated from patients admitted to a tertiary Hospital in Kuantan, Malaysia - Bariman, Mohammad Hanif; Mustafa Mahmoud, Mohammed Imad Al-Deen; Hamzah, Hairul Aini (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Introduction: Methicillin-resistant Staphylococcus aureus is globally a major public health threat. Resistance to methicillin originates from a modified protein (PBP2a) encoded by the mecA gene. The PVL gene as an important virulence factor increases the pathogenicity of MRSA. Epidemiology and characteristics of MRSA differ in different geographical regions. This study was conducted to characterize and determine the antibiotic susceptibility profile of MRSA strains isolated from patients in Hospital Tengku Ampuan Afzan, Pahang, Malaysia and to detect the presence of the mecA and PVL genes in the isolates. Materials and methods: In this study a total of 36 isolates of MRSA have been collected during a period of three months (1stFebruary –30thApril 2018). The susceptibility pattern of the isolates to ten different commonly used antibiotics were determined and the target genes were addressed by real-time PCR experiment. Results: Based on the identifying criteria, 44.4% of the isolates were CA-MRSA, and 55.5% were HA-MRSA. Resistance to oxacillin, cefoxitin and penicillin was 100%, gentamicin 88.8%, erythromycin 33.3%, tetracycline 77.7%, trimethoprim-sulfamethoxazole 61.1%, clindamycin 13.8%, chloramphenicol 11.1%, but no resistant strain of vancomycin was detected. Most of the isolates were resistant to more than three groups of antibiotics. Realtime PCR revealed that all the isolates were mecA positive and 4 isolates were PVL-positive. PVL-positive strains were CA-MRSA and susceptible to clindamycin. Conclusion: The study confirms multi-drug resistant MRSA in the study area, and shows that resistance to methicillin is mecA mediated. PVL carrier strains were present and related to CA-MRSA strains of the isolates.